Comparison of Ultrasonographic Estimated Fetal Weight at Term with Actual Birth Weight in Punjab - Asadullah, Zeeshan Haider, Muhammad Athar Shams Rana, Syed Muhammad Yousaf Farooq, Saad Qayyum, Muhammad Amir Bilal, Fatima Binte Mustafa, Ramsha Shahbaz, Ahsan Nawaz, Muhammad Zain Ul Abidin, Ramsha Zafar, Samia Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The fetus is thought to have an inherent growth potential that under normal circumstances, yields a healthy newborn of appropriate size. Knowledge of weight of fetus in intrauterine life is important for the obstetrician to decide the management plan for delivery whether it would be vaginal or cesarean section. Aim: To compare estimated fetal weight on ultrasound at term with actual birth weight in Bahawalnagar Punjab. Methodology: A cross sectional analytical study was conducted at Tahir Medical Complex Haroon Abad district Bahawalnagar. Data of 200 participants were designated done suitable sample method. SPSS version 21.0 was used for data analysis. Results: out of total number of 200 pregnant women, mean±S. D of estimated fetal weight were 3245.8150±17.53151, Mean ±S. D of actual birth weight were 3260.7700±17.80643. Mean±S.D of Biparietal diameter were 9.2325±0.23428. The minimum and maximum values were 8.70 and 9.76 respectively. Two hundred pregnant females were included in this study. Conclusion: This study indicates that estimation of Birth weight clearly has a role in management of labor and delivery in a term pregnancy. Among term singleton cephalic pregnancies studied, fetal weight estimation using Hadlock’s formula is comparable to ultrasound estimates for predicting the actual birth weight within 10%. This study also revealed the mean estimated weight through ultrasound were similar to actual weight. Our results indicated the diagnostic accuracy of ultrasound in estimation of birth weight to be considerably significant therefore it is a reliable modality for estimating fetal weight using the Biparietal diameter, femur length and abdominal circumference as compared to actual birth weight. Keywords: Expected Fetal weight, actual fetal weight, Biparietal diameter, abdominal circumferences, femur length.